2014
DOI: 10.1037/a0036673
|View full text |Cite
|
Sign up to set email alerts
|

Trust at zero acquaintance: More a matter of respect than expectation of reward.

Abstract: Trust is essential for a secure and flourishing social life, but many economic and philosophical approaches argue that rational people should never extend it, in particular to strangers they will never encounter again. Emerging data on the trust game, a laboratory economic exchange, suggests that people trust strangers excessively (i.e., far more than their tolerance for risk and cynical views of their peers should allow). What produces this puzzling "excess" of trust? We argue that people trust due to a norm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 127 publications
9
173
4
Order By: Relevance
“…Perceptions of trustworthiness were randomly manipulated by informing participants of each target's alleged decision as a trustee in a one-shot binary trust game, as has been used previously in research (Dunning, Anderson, Schl€ osser, Ehlebracht, & Fetchenhauer, 2014;Eckel & Wilson, 2004;Fetchenhauer & Dunning, 2009;Snijders & Keren, 2001). The game was described as follows: Person A (the trustor) was given €5 by the experimenter and could freely decide whether to send this €5 to Person B (i.e., the trustee) or to keep the €5 and exit the interaction.…”
Section: Targets' Trustworthinessmentioning
confidence: 99%
“…Perceptions of trustworthiness were randomly manipulated by informing participants of each target's alleged decision as a trustee in a one-shot binary trust game, as has been used previously in research (Dunning, Anderson, Schl€ osser, Ehlebracht, & Fetchenhauer, 2014;Eckel & Wilson, 2004;Fetchenhauer & Dunning, 2009;Snijders & Keren, 2001). The game was described as follows: Person A (the trustor) was given €5 by the experimenter and could freely decide whether to send this €5 to Person B (i.e., the trustee) or to keep the €5 and exit the interaction.…”
Section: Targets' Trustworthinessmentioning
confidence: 99%
“…Correspondingly, it has recently been argued—and supported in a series of different experiments—that people trust “excessively” because of the power of injunctive norms (Dunning, Anderson, Schlösser, Ehlebracht, and Fetchenhauer, ). By definition, “injunctive norms are those that drive behavior through a feeling that one ‘should’ or ‘ought’ to act a certain way, and can be differentiated from mere preferences or attitudes—that is, how people might want to behave” (Anderson and Dunning, , p. 724).…”
mentioning
confidence: 96%
“…Regarding the decision to trust, the idea hence is that people trust strangers not because they really want to—that is, based on a preference—but rather because they believe they should, thus primarily adhering to an injunctive norm. In what we consider the most striking test of this relatively bold claim (Dunning et al, ; Study 4), participants—playing the trustor in a continuous trust game —were asked not only for a decision (i.e., to indicate the amount they do entrust to the trustee) but also for a judgment on what they should and their preference in terms of what they want to entrust (in the following referred to as should‐trust and want‐trust, respectively). Implying an injunctive norm as the primary driver of the decision to trust, participants' actual trust level more closely resembled their should‐trust judgments than their want‐trust preferences.…”
mentioning
confidence: 99%
“…He found it a predicted behavior independent of preferences, attitudes, and social norms. Similarly, Dunning et al () found that whether people want to trust another person and whether they think they should trust that person independently predicted the decision to trust.…”
Section: The Empirical Signatures Of Normsmentioning
confidence: 96%